Effect of Contract Management Phases on Supply Chain Performance among Manufacturing Firms in Nairobi County, Kenya - Kamau, Peter; Mburu, David (International Journal of Supply Chain Management, 2023)
Purpose: Contract management entails process which ensures parties to the contract undertake the contracts as per the objectives and obligations in the contract. Contract management also involves execution of roles and responsibilities through creation of conducive working relationship to all parties in the agreement. The objective of the study was to establish effect of contract management phases on supply chain performance among manufacturing firms in Nairobi County. Methodology: The population of the study was manufacturing companies which are based in Nairobi, Kenya. Nairobi has 640 manufacturing firms. The sample size of this study consisted of 246 supply chain managers in manufacturing firms in the Nairobi, obtained through stratified sampling and randomly selected. Self-administered questionnaire were used to collect data from the respondents. The quantitative data was coded and grouped into to various categories, percentages, frequencies, means were derived and presentation done through tables for compiling the study. Findings: The study found that pre-contract phase, solicitation, contract execution phase, post award phase influenced supply chain performance as per correlation analysis. The findings indicted buyer specifications are emphasized at pre-contract stage, the contract is signed at execution stage and deliverable during post ward phase and all the stages are crucial for supply chain performance at manufacturing firms. The study concludes that manufacturing firms depend highly on the clear contract singing and fulfillment of the contractual obligations by all parties across the phases. The study also concludes that the success of the firm will depend on efficiency in supply chain therefore; the management should ensure that there are no lapses in the procurement process. Unique Contribution to Theory, Practice and Policy: The study recommends that there is need for manufacturing firms in Kenya to invest in constant training of their employees on effective contract management across all the phases to enhance their performance. The study also recommends that manufacturing firms in Kenya should put in place appropriate measures that ensure that potential risks regarding contract management phases, detected in advance, and mitigated to enhance operational performance.